Telehealth in paediatric orthopaedic surgery in Queensland: a 10‐year review. Issue 12 (18th July 2014) - Rowell, Philip D.; Pincus, Paul; White, Megan; Smith, Anthony C.
Abstract Background Telemedicine is a patient consultation method commonly available to patients in rural and remote areas throughout Australia. Its use in paediatric orthopaedics has been rarely described. The primary aim of this study was to identify the patient cohort accessing the orthopaedic paediatric telehealth service through the Royal Children's Hospital Queensland, so as to better allocate this resource. The secondary aims were to identify the orthopaedic conditions the patients utilizing this service suffered and to follow‐up on treatment outcomes to potentially assess clinical benefit. Method A retrospective review of prospectively collected data of paediatric orthopaedic patients consulted using telehealth at the Royal Children's Hospital, Queensland over a 10‐year period between January 2004 and September 2012 was conducted. Results One hundred and twenty‐six patient records were assessed with a mean age of 6 years. Results showed that 40% of patients seen using telehealth in paediatric orthopaedics had documented cerebral palsy, an intellectual disability or congenital syndrome. Common paediatric orthopaedic conditions were seen, with lower limb malalignment being the most common presenting complaint. About 58% of patients were seen exclusively via telehealth and did not require in‐person consultation or operative therapy. Conclusion We found that the orthopaedic telepaedriatic consultation service at the Royal Children's Hospital reviewed a large proportion of patients with a known disability. We believe there is a role for telehealth medicine for all patients; however, we propose that even greater benefit can be obtained from telehealth consultation in patients with a disability where the cost and inconvenience of patient transport is considerably increased.